2002
DOI: 10.1038/sj.bjc.6600516
|View full text |Cite
|
Sign up to set email alerts
|

A phase I and pharmacokinetic study of MAG-CPT, a water-soluble polymer conjugate of camptothecin

Abstract: Polymeric drug conjugates are a new and experimental class of drug delivery systems with pharmacokinetic promises. The antineoplastic drug camptothecin was linked to a water-soluble polymeric backbone (MAG-CPT) and administrated as a 30 min infusion over 3 consecutive days every 4 weeks to patients with malignant solid tumours. The objectives of our study were to determine the maximal tolerated dose, the dose-limiting toxicities, and the plasma and urine pharmacokinetics of MAG-CPT, and to document anti-tumour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(51 citation statements)
references
References 16 publications
1
47
0
3
Order By: Relevance
“…In contrast to the hints of activity seen here, a related strategy using a polymer carrier to deliver the topoisomerase I inhibitor camptothecin (PNU166148) recently reported negative results in a phase I and pharmacokinetic study involving 23 patients with various types of cancer (6 colorectal, 4 unknown primary, 2 each head and neck, NSCLC, renals and one of each adrenal, cervical, oesophageal, Ewing's, gastric, mesothelioma and prostate) (23). The linkage of camptothecin to the polymer carrier was designed for pHcatalysed esterolytic cleavage, in contrast to the proteasebased release of doxorubicin employed here, making it hard to compare the pharmacology of the two drug conjugates.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast to the hints of activity seen here, a related strategy using a polymer carrier to deliver the topoisomerase I inhibitor camptothecin (PNU166148) recently reported negative results in a phase I and pharmacokinetic study involving 23 patients with various types of cancer (6 colorectal, 4 unknown primary, 2 each head and neck, NSCLC, renals and one of each adrenal, cervical, oesophageal, Ewing's, gastric, mesothelioma and prostate) (23). The linkage of camptothecin to the polymer carrier was designed for pHcatalysed esterolytic cleavage, in contrast to the proteasebased release of doxorubicin employed here, making it hard to compare the pharmacology of the two drug conjugates.…”
Section: Discussionmentioning
confidence: 98%
“…The polymer carrier also permits incorporation of membrane active peptides or targeting agents into the conjugate structure, the latter designed to enhance receptor-mediated uptake into tumour cells or organs containing tumour metastases, and increase the exposure of the tumour to active drug while minimizing exposure of normal tissues (31). Thoughtful design of macromolecular drug conjugates should yield a range of new approaches to cancer treatment with potentially significant benefits, and several have already progressed as far as clinical evaluation in phase I studies (23,(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…When CPT was conjugated to linear PEG, the PK profiles of the released CPT in animals (32) and humans (33,34) showed the same form of the dynamics as observed for CRLX101. Likewise, the MAG-CPT gave released CPT dynamics of the same type (35,36). However, the polymeric micelle of SN-38 shows the same behavior for released SN-38 in animals (37) and humans (28), as does PEG-bound SN-38 in animals (38) and humans (39).…”
Section: Discussionmentioning
confidence: 99%
“…Results presented in an earlier clinical study showed serious bladder toxicity which became dose limiting. Patients with higher plasma AUC values had the more severe symptoms of renal toxicity [54].…”
Section: Hmpa Copolymer-camptothecin (Mag-cpt Pnu166148) and Hmpa Comentioning
confidence: 99%